Obesity and its determinants among adolescents and young adults in Bangladesh: Evidence from a nationwide study (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Limited studies explored the determinants of obesity among Bangladeshi youth.Aims: To estimate the prevalence of obesity and identify socio-demographic, lifestyle, and metabolic risk factors among Bangladeshi adolescents and young adults.Method: This is a post-hoc analysis of a nationwide study that included 2300 young [adolescents: 10-18 years, n=1118 and young adults: 19-34 years, n=1182] by multistage random sampling during March-August 2024. Obesity among adolescents was defined by BMI percentiles (overweight 85th–94th, obesity ≥95th), while in adults by BMI cut-offs (overweight 23–24.9 kg/m², obesity ≥25 kg/m²). Data on lifestyle, family, and socioeconomic history were collected. Blood pressure (BP), plasma glucose, and lipid profile were measured.Results: The prevalence of overweight/obesity was 29.2% (overweight 11.6%, obesity 17.6%), higher among young adults (43.8%) vs. adolescents (13.6%), and in urban areas (38.2%) vs. rural areas (21.1%). In both adolescents and young adults, overweight/obesity was associated with higher wealth index (OR 3.3, 95% CI 2.4–4.8 and 1.9, 95% CI 1.5–2.4 respectively), urban residence (OR 2.9, 95% CI 2.1–4.2 and 1.5, 95% CI 1.2–1.9 respectively), and late bedtime (OR 3.0, 95% CI 2.1–4.3 and 1.3, 95% CI 1.0–1.6 respectively). In addition, overweight/obesity was associated with increased screen time (OR 2.1, 95% CI 1.5–2.9) and short sleep duration (OR 2.2, 95% CI 1.5–3.2) in adolescents while frequent meals outside home (OR 1.3, 95% CI 1.0–1.7) and female gender (OR 1.4, 95% CI 1.1–1.8) in young adults. Elevated BP, acanthosis, and dyslipidemia were associated with overweight/obesity in both groups and diabetes in young adults (all p